Transformational leadership style, competence, and employee involvement on employee performance hotel grandhika semarang - Hanandriati, Bethary; Nugraheni, Krisnawati Setyaningrum (International Journal on Social Science, Economics and Art, 2024)
This research is a pilot effort for companies in the hospitality sector to maintain the performance of the hotel they lead. How transformational leadership style, competence and employee involvement can affect the performance of Grandhika Semarang hotel employees. Employee performance indicators are a sense of meaning, a sense of security, a feeling of availability. This study used quantitative methods, data collection using a questionnaire involving Grandhikan hotel employees who were forty-four respondents. Use Multiple linear regression analysis to analyze data and test hypotheses. The results of the first variable study show that transformational leadership style has a positive effect on employee performance. The second variable shows that competence has a positive effect on employee performance. The third variable shows that employee engagement has a positive effect on employee performance